Defining attractive cities with focus on social sustainability and aesthetics; examination of the redevelopment of Selma Lagerlöfs torg - Engnell, Emma (My University, 2025)
Creating attractive cities is a complex process, where the urban environments play a central role in shaping the everyday experiences of their inhabitants. The surroundings affect people's social interactions, economic opportunities and overall quality of life. The aim of this study is to define what the concept of attractiveness in urban spaces is, with focus on aesthetics and social sustainability. This is examined through a literature study of urban theories and policy documents, particularly policies of the New European Bauhaus (NEB), Gestaltad Livsmiljö (GL), and the Architectural Policy of Gothenburg (AP), and the urban theory Life between buildings by Jan Gehl. Attractiveness is further studied through a case study at Selma Lagerlöfs torg in Gothenburg. This case study compares perceptions from both a project management perspective and from a residential perspective after the redevelopment. This was done through an interview study with 10 main contributors to the project, and site visits with a survey study, which was answered by 59 residents in the area. The results of this study show that an attractive city is not solely characterized by visual qualities, but also by its capacity to promote social sustainability, inclusiveness, and aesthetics. To plan an attractive city the process of urban development must be an iterative, inclusive, human centred and context aware process, creating inclusivity with the contemporary and future locals in the area. Selma Lagerlöfs torg was overall a successful project, appreciated both by main contributors and by locals in the area. However, none of the policy frameworks were consciously used when planning the redevelopment, only the theories by Gehl were partly considered. This concludes, that while policy and theory provide valuable guidance true attractiveness ultimately depends on how spaces are perceived, used, and lived in by diverse groups over time.
Keywords: Attractive city, New European Bauhaus, Gestaltad livsmiljö, Architectual policy of Gothenburg, Jan Gehl, Selma Lagerlöfs torg.